The Verbal Influence of Husband and Wife on The Verbal of Couple and Children in The Family (Journal of Family Sciences, 2024)
Interaction among family members can be in the form of verbal interaction. A bad verbal partner has an impact on verbal in the family. The purpose of this study was to examine the relationship and test the influence of family characteristics, husband-wife verbal, on partner and child verbal. This study used a cross-sectional design. The population of this research is husband/wife in Indonesia. The number of respondents was 113 people. The results show that the income of one husband and wife has a significant positive relationship with verbal affection for their partner and their children. Verbal violence of one partner has a significant positive relationship with verbal abuse of their children. A husband/wife's verbal affection for a partner has a significant positive relationship with verbal affection for children. Respondents' verbal violence to their partners had a significant positive effect on verbal violence toward children. Respondents' verbal affection for their partner has a significant positive effect on verbal affection for children. The negative diction used is stupid, and the positive meaning is dear. In conclusion, husband/wife's verbal relationship and influence on their verbal to their children.